The Quest for a Stable Disk - J. A. Sellwood; R. G. Carlberg (The Astrophysical Journal)
The majority of disk galaxies manifest spirals and/or bars that are believed to result from dynamical instabilities. However, some galaxies have featureless disks, which are therefore inferred to be dynamically stable. Yet despite many years of effort, theorists have been unable to construct realistic models of galaxy disks that possess no instabilities and therefore could remain featureless. This conclusion has been reached through simulations for the most part, some of which have been confirmed by linear stability analyses. A. Toomre (1981) claimed that the Mestel disk, embedded in an equal-mass halo, is a notable counterexample, but his prediction of stability could not be reproduced in simulations, due to complicated nonlinear effects that caused secular growth of Poisson noise–driven disturbances until strong features emerged. Here, we revisit this issue and show that simply eliminating the most nearly circular orbits from Toomre's disk model can inhibit troublesome secular growth. We also present both 2D and 3D simulations of particle disks that remain featureless for over 50 orbit periods. We report that spiral evolution naturally depletes circular orbits and that the radial velocity distribution in the featureless disks of S0 galaxies should have negative kurtosis.